Monitoring of postoperative neutrophil-to-lymphocyte ratio, D-dimer, and CA153 in: Diagnostic value for recurrent and metastatic breast cancer - Ren, Zhiyao; Yang, Jing; Liang, Jiahui; Xu, Yunfeng; Lu, Guanda; Han, Yanxun; Zhu, Jie; Tan, Husheng; Xu, Tao; Ren, Min (Frontiers in Surgery, 2023)
Objective: To assess the value of monitoring of postoperative neutrophil-to-lymphocyte ratio (NLR), D-dimer and carbohydrate antigen 153 (CA153) for diagnosis of breast cancer (BC) recurrence and metastasis. Materials/Methods: A cohort of 252 BC patients who underwent surgery at the First Affiliated Hospital of Anhui Medical University between August 2008 and August 2018 were enrolled into this retrospective study. All patients were examined during outpatient follow-up every three months for five years post-operation and every six months thereafter. Recurrence or metastasis was recorded for 131 patients but not for the remaining 121. Retrospective analysis of hematological parameters and clinicopathological characteristics allowed comparison between the 2 groups and evaluations of these parameters for the recurrent and metastatic patients. Results: Lymph node metastasis, higher Tumor Node Metastasis (TNM) staging and higher histological grade correlated with BC recurrence and metastasis (p<0.05). Statistical diﬀerences were found in absolute neutrophil count (ANC), absolute lymphocyte count (ALC), CEA, CA153, D-dimer, NLR, platelet-to-lymphocyte ratio (PLR) and monocyte-to-lymphocyte ratio (MLR) between the recurrent and metastatic and control groups (p<0.05). Logistic regression analysis showed that CA153, D-dimer, NLR and TNM staging were risk factors for BC recurrence and metastasis (p<0.05). Combined values for the NLR, D-dimer and CA153 had good diagnostic value giving the highest area under the curve (AUC) of 0.913. High NLR, D-dimer and CA153 values were significantly associated with recurrence and metastasis at multiple sites, lymph node metastasis and higher TNM staging (p<0.05). Patients with high CA153 were more likely to have bone metastases (p<0.05) and those with high D-dimer were prone to lung metastasis (p<0.05). With increasing length of the post-operative period, the possibility of liver metastases gradually decreased while that of chest wall recurrence gradually increased (p<0.05). Conclusion: Monitoring of postoperative NLR, D-dimer and CA153 is a convenient, practical method for diagnosing BC recurrence and metastasis. These metrics have good predictive value in terms of sites of recurrence and metastasis and of the likelihood of multiple metastases.